THE INFLUENCE OF LEG MUSCLE EXPLOSIVE POWER ON HAND EYE COORDINATION WITH SMASH ACCURACY OF ATHLETES VOLLEYBALL ATHLETES OF SOUTHEAST ACEH DISTRICT - Irwansyah, Orbit; Ladipin, Ladipin (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The problem in this study is that the accuracy of Smash of men's Volleyball athletes in Southeast Aceh Regency is not so good. This study aims to determine the effect of leg muscle explosive power on hand eye coordination with the accuracy of smash volleyball for men's Volleyball athletes in Southeast Aceh Regency. This type of research is quantitative. The population in this study was 25 people, the sample was taken using the total sampling technique, so the total sample was 25 people. Data were collected using measurements of the three variables. The variable of leg muscle explosive power using vertical jump test and hand eye coordination using balwerfen and fangen, while smash accuracy using smash accuracy test. The results showed that leg explosive power had a significant influence on smash accuracy with a score above the average group of 10 people, Hand eye coordination has a significant influence on smash accuracy with scores above the average group as many as 13 people, Furthermore, limb explosive power and hand eye coordination together have a significant influence on smash accuracy and are accepted empirically as many as 12 people.